Analisis Kesuksesan Sistem Informasi Absensi Guru SD Pusdai Sumedang Menggunakan Model Delone & Mclean - yati novita, surendi; Novita, Yati; Supiandi, Apip; Wintana, Dede (LPPM Universitas Bina Sarana Informatika, 2023)
With the passage of time and the development of human resources, SD Pusdai Sumedang now uses an Android-based attendance application to facilitate attendance. This research was conducted with the aim of knowing the success of the SD Pusdai Sumedang teacher attendance information system using the Delone & Mclean model, which includes the variables of system quality, information quality, service quality, usage, user satisfaction and system benefits. The number of respondents was 24 teachers and SD Pusdai Sumedang staff. Data analysis methods used in the instrument test are convergent validity test, discriminant validity test, R Square test, F Square test, and t-test. The test was carried out by calculating the PLS-SEM with the smartpls 4 tool. Based on the results of the study, the following conclusions can be drawn: (1) System quality has a significant effect on the use of the attendance application; (2) There is a significant influence between the use of the present-request system; (3) There is no significant influence between information quality, service quality, use, then system quality, information quality, service quality, usage on user satisfaction and user satisfaction with system usability.